1997
DOI: 10.3109/10408449709021617
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of DNA Double-Strand Breaks in Toxicity and Carcinogenesis

Abstract: DNA double-strand breaks are associated with various endogenous processes, such as transcription, recombination, replication, and with the process of active cell death, which aims to eliminate cells. In addition, DNA double-strand breaks can be induced by irradiation, exposure to chemicals, increased formation of reactive oxygen species, and, indirectly, during repair of other types of DNA damage or as a consequence of extranuclear lesions. In addition to the neutral filter elution of DNA, the recently introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 115 publications
0
56
0
2
Order By: Relevance
“…We also demonstrated that deregulated Pol b results in modi®cations at the chromosomal level, the ampli®cation of the level of DNA breaks and aberrations induced by radiation, which have been speculated to play a role in the process of radiation carcinogenesis (Vamvakas et al, 1997). This suggests that high level of Pol b, which magnify these chromosomal modi®cations, may therefore predispose the minority of the cell population which survives the radiotherapy for high tumour incidence when exposed to radiations.…”
Section: Discussionmentioning
confidence: 72%
“…We also demonstrated that deregulated Pol b results in modi®cations at the chromosomal level, the ampli®cation of the level of DNA breaks and aberrations induced by radiation, which have been speculated to play a role in the process of radiation carcinogenesis (Vamvakas et al, 1997). This suggests that high level of Pol b, which magnify these chromosomal modi®cations, may therefore predispose the minority of the cell population which survives the radiotherapy for high tumour incidence when exposed to radiations.…”
Section: Discussionmentioning
confidence: 72%
“…RONS-induced DNA lesions such as base damage, single-strand breaks, and double-strand breaks (DSBs) can be cytotoxic and thus damaging to host tissue function (9,10). DSBs are one of the most toxic forms of DNA damage (11,12). In response to DSBs, the ataxia telangiectasia mutated (ATM) kinase pathway is activated, leading to Ser-139 phosphorylation of histone H2AX, forming γH2AX.…”
mentioning
confidence: 99%
“…Elevated top1 protein levels increase the frequency of cleavable complexes (Pommier, 1996), thereby increasing DNA damage. As a consequence, DNA single-strand breaks tend to accumulate, and it is most likely that attempts to replicate and/or repair the damaged DNA enhances the formation of DNA double-strand breaks (Vamvakas et al, 1997).…”
mentioning
confidence: 99%